Austenitic alloy material
By optimizing the chemical composition of the austenite alloy material, especially increasing the content of Mn, Cu, Cr, Ni and Mo and reducing the content of Si, and through specific element ratios and content ranges, the problems of nitriding resistance and grain boundary cracks of alloy materials in high-temperature ammonia environments are solved, and efficient nitriding resistance and crack suppression effects are achieved.
Patent Information
- Application Number
- CN202380065670.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-15
- Publication Date
- 2025-04-22
AI Technical Summary
When using austenite alloy material in a high-temperature ammonia environment, the formation of a nitride layer is easily promoted, resulting in a decrease in the creep strength of the alloy, and it is difficult to obtain sufficient nitride resistance.
By optimizing the chemical composition of the alloy, ensure that the content of Si is contained in Mn, Cu, Cr, Ni and Mo, and the content of Si is reduced, and the specific element ratio and content range (such as Fn1 is less than 20 and Fn2 is more than 21 but less than 50) is achieved to improve the nitriding resistance of the alloy and inhibit the generation of grain boundary cracks.
In the high-temperature ammonia environment, the nitriding resistance of the austenite alloy material is significantly improved, and the grain boundary cracks in the surface layer are effectively suppressed, ensuring the creep strength and toughness of the alloy.
Smart Images

Figure CN119866383A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to alloy materials, and more particularly to austenitic alloy materials. Background Art
[0002] Recently, hydrogen has attracted attention as a clean energy source that does not produce carbon dioxide. Hydrogen is a gas at room temperature and pressure. If it needs to be liquefied for transportation, it needs to be kept at an extremely low temperature of below -253°C. Therefore, it is difficult to transport hydrogen alone.
[0003] For this reason, the use of ammonia as a carrier of hydrogen is being studied. Ammonia contains about 18% hydrogen by mass and liquefies at -33°C, which is higher than the boiling point of hydrogen. Therefore, the transportation of ammonia as a carrier of hydrogen and the separation of hydrogen from the ammonia at the transportation destination are being studied to utilize hydrogen as energy.
[0004] To separate hydrogen from ammonia, a catalyst is required to decompose ammonia in a high temperature environment of about 600°C under normal pressure. In the following description, an environment of about 600°C, normal pressure, and ammonia atmosphere is referred to as a "high temperature ammonia environment". For this purpose, an alloy material that can withstand use in a high temperature ammonia environment is required.
[0005] As alloy materials suitable for high-temperature ammonia environments for hydrogen production, austenitic alloy materials used in chemical plants can be considered. This is because chemical plants are high-temperature environments equivalent to high-temperature ammonia environments. Austenitic alloy materials used in chemical plants are disclosed, for example, in Japanese Patent Publication No. 2017-088957 (Patent Document 1). The chemical composition of the alloy material disclosed in the document contains, by mass%, C: 0.02-0.12%, Si: 0.1-2%, Mn: 0.1-3%, P: 0.04% or less, S: 0.02% or less, Cr: 20-26%, Ni: more than 26% and less than 35%, W: 1-5.5%, V: 0.01-1%, Nb: 0.01-1%, B: 0.0005-0.008%, Mo: less than 0.3%, Al: 0.001-0.3%, Cu: less than 0.3%, Ti: less than 0.01%, N: more than 0.13% and less than 0.35%, REM: 0.003-0.10%, etc. Patent document 1 states that when the above-mentioned austenitic alloy material is used, excellent creep strength can be obtained in use under high temperature environment.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-088957 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, it has recently been found that when an austenitic alloy material is used in the above-mentioned high-temperature ammonia environment, nitridation on the surface of the alloy material is promoted. If the formed nitrided layer becomes thicker, the alloy part other than the nitrided layer becomes thinner. In this case, the creep strength at high temperature is reduced. Therefore, the austenitic alloy material used in the high-temperature ammonia environment is required to have excellent nitridation resistance.
[0011] An object of the present invention is to provide an austenitic alloy material having excellent nitriding resistance in a high-temperature ammonia environment.
[0012] Solutions for solving problems
[0013] The chemical composition of the austenitic alloy material of the present invention contains, by mass%,
[0014] C: greater than 0 and less than 0.200%,
[0015] Si: more than 0 and 3.00% or less,
[0016] Mn: more than 0 and less than 3.00%,
[0017] P: greater than 0 and less than 0.050%,
[0018] S: greater than 0 and less than 0.050%,
[0019] Ni: 40.00~80.00%, and
[0020] Cr: 10.00~35.00%,
[0021] Also contains the freedom to choose
[0022] Sn: greater than 0 and less than 0.1000%,
[0023] Zn: more than 0 and less than 0.0100%,
[0024] Pb: more than 0 and less than 0.0100%,
[0025] Sb: more than 0 and less than 0.0100%,
[0026] As: greater than 0 and less than 0.0010%, and
[0027] Bi: one or more selected from the group consisting of more than 0 and 0.0010% or less,
[0028] Further comprising
[0029] Cu: more than 0 and less than 5.00%,
[0030] Mo: more than 0 and less than 20.00%,
[0031] Co: more than 0 and 3.00% or less,
[0032] W: greater than 0 and less than 7.00%,
[0033] Ti: more than 0 and less than 1.00%,
[0034] Nb: more than 0 and less than 0.10%,
[0035] V: greater than 0 and less than 0.50%,
[0036] B: greater than 0 and less than 0.0050%,
[0037] N: greater than 0 and less than 0.200%,
[0038] Rare earth elements: greater than 0 and less than 0.100%,
[0039] Al: more than 0 and 0.500% or less,
[0040] Ca: more than 0 and 0.0100% or less, and
[0041] Mg: one or more selected from the group consisting of more than 0 and 0.0150% or less,
[0042] The balance is Fe and impurities.
[0043] Fn1 defined by formula (1) is less than 20,
[0044] Fn2 defined by formula (2) is greater than 21 and less than 50,
[0045] Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1)
[0046] Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2)
[0047] The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
[0048] Effects of the Invention
[0049] The austenitic alloy material of the present invention has excellent nitriding resistance in a high-temperature ammonia environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a graph showing the relationship between Fn1 and the nitrided layer depth (μm) when an alloy material having the content of each element in the chemical composition within the range of the present embodiment is kept at 600° C. in a 100% ammonia atmosphere for 25 hours. DETAILED DESCRIPTION
[0051] The present inventors have studied alloy materials that can obtain excellent nitriding resistance when used in a high-temperature ammonia environment. First, the present inventors have studied elements that improve nitriding resistance in a high-temperature ammonia environment. As a result, the present inventors have found that Mn, Cu, Cr, Ni and Mo improve the nitriding resistance of the alloy material in a high-temperature ammonia environment, while Si reduces the nitriding resistance of the alloy material in a high-temperature ammonia environment.
[0052] For this purpose, alloy materials have been studied from the viewpoint of chemical composition, taking into account the above-mentioned elements (Mn, Cu, Cr, Ni, and Mo) that improve nitriding resistance and the element (Si) that reduces nitriding resistance. As a result, the present inventors have found that if the present invention contains, by mass%, C: greater than 0 and 0.200% or less, Si: greater than 0 and 3.00% or less, Mn: greater than 0 and 3.00% or less, P: greater than 0 and 0.050% or less, S: greater than 0 and 0.050% or less, Ni: 40.00-80.00%, Cr: 10.00-35.00%, and further contains one or more selected from the group consisting of Sn: greater than 0 and 0.1000% or less, Zn: greater than 0 and 0.0100% or less, Pb: greater than 0 and 0.0100% or less, Sb: greater than 0 and 0.0100% or less, As: greater than 0 and 0.0010% or less, and Bi: greater than 0 and 0.0010% or less, and further contains Cu: An austenitic alloy material containing at least one of the group consisting of greater than 0 and less than 5.00%, Mo: greater than 0 and less than 20.00%, Co: greater than 0 and less than 3.00%, W: greater than 0 and less than 7.00%, Ti: greater than 0 and less than 1.00%, Nb: greater than 0 and less than 0.10%, V: greater than 0 and less than 0.50%, B: greater than 0 and less than 0.0050%, N: greater than 0 and less than 0.200%, rare earth elements: greater than 0 and less than 0.100%, Al: greater than 0 and less than 0.500%, Ca: greater than 0 and less than 0.0100%, and Mg: greater than 0 and less than 0.0150%, with the balance being Fe and impurities, may have excellent nitriding resistance even in a high-temperature ammonia environment.
[0053] However, even the austenitic alloy material having the above chemical composition may not have sufficient nitriding resistance in a high-temperature ammonia environment. Therefore, the present inventors conducted further research.
[0054] Here, the present inventors believe that when the content of the above-mentioned elements (Mn, Cu, Cr, Ni and Mo) that improves nitriding resistance and the content of the element (Si) that reduces nitriding resistance meet a prescribed relationship, the nitriding resistance in a high-temperature ammonia environment can be improved. To this end, the present inventors investigated the relationship between the content of the elements (Mn, Cu, Cr, Ni and Mo) that improves nitriding resistance and the content of the element (Si) that reduces nitriding resistance and the depth of the nitrided layer in a high-temperature ammonia environment in an austenitic alloy material that meets the above-mentioned chemical composition. As a result, the present inventors found that if Fn1 defined by formula (1) is less than 20 based on the content of each element (Mn, Cu, Cr, Ni and Mo) that improves nitriding resistance and the content of the element (Si) that reduces nitriding resistance, excellent nitriding resistance can be obtained in a high-temperature ammonia environment.
[0055] Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1)
[0056] The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
[0057] Figure 1 This is a graph showing the relationship between Fn1 and the nitrided layer depth (μm) when an alloy material having the content of each element in the chemical composition within the range of the present embodiment is kept at 600° C. in a 100% ammonia atmosphere for 25 hours. Figure 1 It is produced based on the data obtained in the examples described below. Figure 1 In the alloy material whose contents of each element in the chemical composition are within the range of the present embodiment, when Fn1 is 20 or more, the depth of the nitrided layer when kept at 600°C for 25 hours in a 100% ammonia atmosphere is greater than 30.0 μm. On the other hand, when Fn1 is less than 20, the depth of the nitrided layer when kept at 600°C for 25 hours in a 100% ammonia atmosphere is 15.0 μm or less, which can significantly improve the nitriding resistance.
[0058] As described above, the present inventors have found that excellent nitriding resistance can be obtained in a high-temperature ammonia environment if the austenitic alloy material has the above chemical composition and Fn1 is less than 20. However, it has been found that there is a new technical problem in the austenitic alloy material having the above chemical composition and Fn1 less than 20, that is, in a high-temperature ammonia environment, grain boundary cracks may occur in the surface layer of the alloy material.
[0059] Therefore, the present inventors have conducted further research on a method for suppressing the generation of grain boundary cracks in an austenitic alloy material having the above chemical composition and Fn1 less than 20 in a high-temperature ammonia environment. As a result, it was found that in an austenitic alloy material having the above chemical composition and Fn1 less than 20, if Fn2 defined by formula (2) is greater than 21 and less than 50, excellent nitriding resistance can be obtained in a high-temperature ammonia environment, and the generation of grain boundary cracks in the surface layer can also be sufficiently suppressed.
[0060] Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2)
[0061] The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
[0062] It is not yet clear why the grain boundary cracks in the surface layer can be suppressed under a high-temperature ammonia environment if Fn2 is greater than 21 and less than 50, but the present inventors believe that the reasons are as follows. In the austenitic alloy material having the above-mentioned chemical composition, Sn, Zn, Pb, Sb, As and Bi are all contained in trace amounts and segregate at the grain boundaries of the alloy material under a high-temperature ammonia environment. Therefore, these elements will inhibit the formation of precipitates at the grain boundaries or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface layer of the alloy material under a high-temperature ammonia environment can be suppressed. If Fn2 is less than 21, the above-mentioned effect cannot be fully obtained.
[0063] On the other hand, if Fn2 is greater than 50, Sn, Zn, Pb, Sb, As and Bi will be excessively segregated at the grain boundaries, and the grain boundary strength will be reduced. Therefore, in a high-temperature ammonia environment, grain boundary cracks are likely to occur on the surface of the alloy material.
[0064] If Fn2 is greater than 21 and less than 50, then on the premise that Fn1 is less than 20, the generation of grain boundary cracks can be sufficiently suppressed in the surface layer of the austenitic alloy material in a high-temperature ammonia environment.
[0065] It is also possible that the grain boundary cracks in the surface layer are suppressed by a mechanism different from the above mechanism. However, if Fn2 is greater than 21 and less than 50, the grain boundary cracks in the surface layer can be fully suppressed in a high-temperature ammonia environment, provided that Fn1 is less than 20, as demonstrated in the examples described later.
[0066] Based on the above technical concept, the austenitic alloy material of the present embodiment has been completed. The austenitic alloy material of the present embodiment has the following configuration.
[0067] The chemical composition of the austenitic alloy material of the first constitution contains, in mass %,
[0068] C: greater than 0 and less than 0.200%,
[0069] Si: more than 0 and 3.00% or less,
[0070] Mn: more than 0 and less than 3.00%,
[0071] P: greater than 0 and less than 0.050%,
[0072] S: greater than 0 and less than 0.050%,
[0073] Ni: 40.00~80.00%, and
[0074] Cr: 10.00~35.00%,
[0075] Also contains the freedom to choose
[0076] Sn: greater than 0 and less than 0.1000%,
[0077] Zn: more than 0 and less than 0.0100%,
[0078] Pb: more than 0 and less than 0.0100%,
[0079] Sb: more than 0 and less than 0.0100%,
[0080] As: greater than 0 and less than 0.0010%, and
[0081] Bi: one or more selected from the group consisting of more than 0 and 0.0010% or less,
[0082] Further comprising
[0083] Cu: more than 0 and less than 5.00%,
[0084] Mo: more than 0 and less than 20.00%,
[0085] Co: more than 0 and 3.00% or less,
[0086] W: greater than 0 and less than 7.00%,
[0087] Ti: more than 0 and less than 1.00%,
[0088] Nb: more than 0 and less than 0.10%,
[0089] V: greater than 0 and less than 0.50%,
[0090] B: greater than 0 and less than 0.0050%,
[0091] N: greater than 0 and less than 0.200%,
[0092] Rare earth elements: greater than 0 and less than 0.100%,
[0093] Al: more than 0 and 0.500% or less,
[0094] Ca: more than 0 and 0.0100% or less, and
[0095] Mg: one or more selected from the group consisting of more than 0 and 0.0150% or less,
[0096] The balance is Fe and impurities.
[0097] Fn1 defined by formula (1) is less than 20,
[0098] Fn2 defined by formula (2) is greater than 21 and less than 50,
[0099] Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1)
[0100] Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2)
[0101] The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
[0102] The austenitic alloy material of the second configuration is the austenitic alloy material of the first configuration, wherein:
[0103] The average grain size in μm of the surface layer of the austenitic alloy material is defined as D ave hour,
[0104] Fn3 defined by formula (3) is greater than 0.20,
[0105] Fn4 defined by formula (4) is 1000 to 5000,
[0106] Fn3=Fn2 / D ave (3)
[0107] Fn4=Fn2×D ave (4)
[0108] The austenitic alloy material of the third constitution is the austenitic alloy material of the first constitution or the second constitution, and its chemical composition contains, in mass %,
[0109] C: greater than 0 and less than 0.050%,
[0110] Si: more than 0 and less than 0.50%,
[0111] Mn: more than 0 and less than 0.50%,
[0112] P: greater than 0 and less than 0.025%,
[0113] S: greater than 0 and less than 0.010%,
[0114] Cu: 2.00~4.00%,
[0115] Ni: 44.00~50.00%,
[0116] Cr: 20.00~25.00%,
[0117] Mo: 5.00~7.00%,
[0118] W: 2.00~5.00%, and
[0119] Fe: 12.00~20.00%.
[0120] The austenitic alloy material of the fourth constitution is the austenitic alloy material of the first constitution or the second constitution, and its chemical composition contains, in mass %,
[0121] C: greater than 0 and less than 0.150%,
[0122] Si: 1.00~2.50%,
[0123] Mn: more than 0 and less than 1.00%,
[0124] P: greater than 0 and less than 0.010%,
[0125] S: greater than 0 and less than 0.010%,
[0126] Cu: 1.50-3.00%,
[0127] Cr: 28.00~32.00%,
[0128] Mo: 1.00~3.00%,
[0129] Ti: more than 0 and less than 1.00%, and
[0130] Fe: 2.00~6.00%.
[0131] The austenitic alloy material of the fifth constitution is the austenitic alloy material of the first constitution or the second constitution, and its chemical composition contains, in mass %,
[0132] C: greater than 0 and less than 0.050%,
[0133] Si: more than 0 and less than 0.50%,
[0134] Mn: more than 0 and less than 0.50%,
[0135] P: greater than 0 and less than 0.030%,
[0136] S: greater than 0 and less than 0.015%,
[0137] Cu: more than 0 and less than 0.50%,
[0138] Cr: 27.00~31.00%,
[0139] Fe: 7.00~15.00%, and
[0140] Ni: 58.00~80.00%.
[0141] Hereinafter, the austenitic alloy material of the present embodiment will be described in detail. It should be noted that "%" concerning an element represents mass % unless otherwise specified. In the following description, the austenitic alloy material may also be simply referred to as "alloy material".
[0142] [Characteristics of the Austenitic Alloy Material of the Present Embodiment]
[0143] The austenitic alloy material according to the present embodiment has the following features.
[0144] (Feature 1)
[0145] The chemical composition contains, by mass%, C: greater than 0 and less than 0.200%, Si: greater than 0 and less than 3.00%, Mn: greater than 0 and less than 3.00%, P: greater than 0 and less than 0.050%, S: greater than 0 and less than 0.050%, Ni: 40.00-80.00%, Cr: 10.00-35.00%, and further contains one selected from the group consisting of Sn: greater than 0 and less than 0.1000%, Zn: greater than 0 and less than 0.0100%, Pb: greater than 0 and less than 0.0100%, Sb: greater than 0 and less than 0.0100%, As: greater than 0 and less than 0.0010%, and Bi: greater than 0 and less than 0.0010%. The above further contains one or more selected from the group consisting of Cu: greater than 0 and less than 5.00%, Mo: greater than 0 and less than 20.00%, Co: greater than 0 and less than 3.00%, W: greater than 0 and less than 7.00%, Ti: greater than 0 and less than 1.00%, Nb: greater than 0 and less than 0.10%, V: greater than 0 and less than 0.50%, B: greater than 0 and less than 0.0050%, N: greater than 0 and less than 0.200%, rare earth elements: greater than 0 and less than 0.100%, Al: greater than 0 and less than 0.500%, Ca: greater than 0 and less than 0.0100%, and Mg: greater than 0 and less than 0.0150%, and the balance is Fe and impurities.
[0146] (Feature 2)
[0147] Fn1 defined by formula (1) is less than 20.
[0148] Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1)
[0149] Here, the element symbol in formula (1) is substituted with the content of the corresponding element in mass %. When the element is not contained, "0" is substituted with the corresponding element symbol.
[0150] (Feature 3)
[0151] Fn2 defined by formula (2) is greater than 21 and less than 50.
[0152] Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2)
[0153] Here, the element symbol in formula (2) is substituted with the content of the corresponding element in mass %. When the element is not contained, "0" is substituted with the corresponding element symbol.
[0154] Each feature is described below.
[0155] [About (Feature 1) Chemical composition]
[0156] The chemical composition of the austenitic alloy material according to the present embodiment contains the following elements.
[0157] C: greater than 0 and less than 0.200%
[0158] Carbon (C) generates fine carbides during the use of the alloy material in a high-temperature ammonia environment, thereby improving creep strength. However, if the C content is greater than 0.200%, excessive carbides will be generated at the grain boundaries in a high-temperature ammonia environment. In this case, even if the content of other elements is within the range of this embodiment, grain boundary cracks are easily generated on the surface of the alloy material.
[0159] Therefore, the C content is greater than 0 and is 0.200% or less.
[0160] The lower limit of the C content is preferably 0.001%, more preferably 0.005%, further preferably 0.010%, further preferably 0.020%.
[0161] The upper limit of the C content is preferably 0.180%, more preferably 0.160%, and further preferably 0.150%.
[0162] The preferred range of the C content is, for example, 0.001 to 0.180%, more preferably 0.005 to 0.160%, further preferably 0.010 to 0.150%, and further preferably 0.020 to 0.150%.
[0163] Si: more than 0 and 3.00% or less
[0164] Silicon (Si) deoxidizes the alloy. Si further improves the oxidation resistance of the alloy material in a high-temperature ammonia environment. However, if the Si content is greater than 3.00%, even if the contents of other elements are within the range of this embodiment, grain boundary cracks may occur in a high-temperature ammonia environment.
[0165] Therefore, the Si content is greater than 0 and is 3.00% or less.
[0166] The lower limit of the Si content is preferably 0.01%, more preferably 0.05%, further preferably 0.10%, further preferably 0.30%.
[0167] The upper limit of the Si content is preferably 2.80%, more preferably 2.70%, and further preferably 2.60%.
[0168] The Si content is preferably in the range of, for example, 0.01 to 2.80%, more preferably 0.05 to 2.70%, further preferably 0.10 to 2.60%, and further preferably 0.30 to 2.60%.
[0169] Mn: more than 0 and less than 3.00%
[0170] Manganese (Mn) improves the nitriding resistance of the alloy material in a high-temperature ammonia environment. However, if the Mn content is greater than 3.00%, the creep ductility of the alloy material in a high-temperature ammonia environment will decrease even if the contents of other elements are within the range of this embodiment. Furthermore, the toughness of the alloy material will decrease.
[0171] Therefore, the Mn content is greater than 0 and is 3.00% or less.
[0172] The lower limit of the Mn content is preferably 0.01%, more preferably 0.05%, further preferably 0.10%, further preferably 0.30%.
[0173] The upper limit of the Mn content is preferably 2.80%, more preferably 2.50%, further preferably 2.00%, further preferably 1.50%.
[0174] The preferred range of the Mn content is, for example, 0.01 to 2.80%, more preferably 0.05 to 2.50%, further preferably 0.10 to 2.00%, and further preferably 0.30 to 1.50%.
[0175] P: greater than 0 and less than 0.050%
[0176] Phosphorus (P) is an impurity. If the P content is greater than 0.050%, P will segregate at the grain boundaries in a high-temperature ammonia environment. Therefore, even if the contents of other elements are within the range of this embodiment, the alloy material in a high-temperature ammonia environment may also generate grain boundary cracks.
[0177] Therefore, the P content is greater than 0 and is 0.050% or less.
[0178] The P content is preferably as low as possible. However, excessively reducing the P content will significantly increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.005%.
[0179] The upper limit of the P content is preferably 0.045%, more preferably 0.042%, and further preferably 0.040%.
[0180] The preferred range of the P content is, for example, 0.001 to 0.045%, more preferably 0.002 to 0.042%, and even more preferably 0.005 to 0.040%.
[0181] S: greater than 0 and less than 0.050%
[0182] Sulfur (S) is an impurity. If the S content is greater than 0.050%, S will segregate at the grain boundaries in a high-temperature ammonia environment. Therefore, even if the contents of other elements are within the range of this embodiment, the alloy material in a high-temperature ammonia environment may also generate grain boundary cracks.
[0183] Therefore, the S content is greater than 0 and is 0.050% or less.
[0184] The S content is preferably as low as possible. However, excessively reducing the S content will significantly increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the S content is 0.001%, more preferably 0.002%, and more preferably 0.005%.
[0185] The upper limit of the S content is preferably 0.045%, more preferably 0.040%, and further preferably 0.035%.
[0186] The preferred range of the S content is, for example, 0.001 to 0.045%, more preferably 0.002 to 0.040%, and further preferably 0.005 to 0.035%.
[0187] Ni: 40.00~80.00%
[0188] Nickel (Ni) improves the nitridation resistance of the alloy material in a high-temperature ammonia environment. If the Ni content is less than 40.00%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0189] On the other hand, if the Ni content exceeds 80.00%, even if the contents of other elements are within the ranges of the present embodiment, grain boundary cracks may occur in a high-temperature ammonia environment.
[0190] Therefore, the Ni content is 40.00 to 80.00%.
[0191] The lower limit of the Ni content is preferably 43.00%, more preferably 45.00%, further preferably 50.00%, further preferably 55.00%.
[0192] The upper limit of the Ni content is preferably 75.00%, more preferably 70.00%, further preferably 65.00%, further preferably 60.00%.
[0193] The preferred range of the Ni content is, for example, 43.00 to 75.00%, more preferably 45.00 to 70.00%, more preferably 50.00 to 65.00%, and even more preferably 55.00 to 60.00%.
[0194] Cr: 10.00~35.00%
[0195] Chromium (Cr) improves the nitriding resistance of the alloy material in a high-temperature ammonia environment. If the Cr content is less than 10.00%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0196] On the other hand, if the Cr content exceeds 35.00%, the creep strength of the alloy material in a high-temperature ammonia environment decreases even if the contents of other elements are within the ranges of the present embodiment.
[0197] Therefore, the Cr content is 10.00 to 35.00%.
[0198] The lower limit of the Cr content is preferably 12.00%, more preferably 15.00%, and further preferably 18.00%.
[0199] The upper limit of the Cr content is preferably 33.00%, more preferably 32.00%, further preferably 31.00%, further preferably 30.00%.
[0200] The Cr content preferably ranges from 12.00 to 33.00%, for example, more preferably from 15.00 to 32.00%, further preferably from 18.00 to 31.00%, and further preferably from 18.00 to 30.00%.
[0201] The austenitic alloy material of the present embodiment further includes the first group.
[0202] [Group 1]
[0203] Freedom to choose
[0204] Sn: greater than 0 and less than 0.1000%,
[0205] Zn: more than 0 and less than 0.0100%,
[0206] Pb: more than 0 and less than 0.0100%,
[0207] Sb: more than 0 and less than 0.0100%,
[0208] As: greater than 0 and less than 0.0010%, and
[0209] Bi: one or more selected from the group consisting of more than 0 and 0.0010% or less,
[0210] Sn, Zn, Pb, Sb, As, and Bi all suppress grain boundary cracking near the surface layer of the alloy material in a high-temperature ammonia environment.
[0211] Sn: greater than 0 and less than 0.1000%
[0212] Tin (Sn) may not be contained. That is, the Sn content may be 0%.
[0213] When this element is contained, that is, when the Sn content is greater than 0%, Sn will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated Sn inhibits the formation of precipitates at the grain boundaries, or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as Sn is contained in a small amount, the above effect can be achieved to a certain extent.
[0214] However, if the Sn content is greater than 0.1000%, Sn will be excessively segregated at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. At this time, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, it will promote grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment.
[0215] Therefore, the Sn content is greater than 0 and is 0.1000% or less.
[0216] The lower limit of the Sn content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003%.
[0217] The upper limit of the Sn content is preferably 0.0700%, more preferably 0.0500%, and further preferably 0.0450%.
[0218] The Sn content is preferably in the range of, for example, 0.0001 to 0.0700%, more preferably 0.0002 to 0.0500%, and even more preferably 0.0003 to 0.0450%.
[0219] Zn: more than 0 and less than 0.0100%
[0220] Zinc (Zn) may not be contained. That is, the Zn content may be 0%.
[0221] When this element is contained, that is, when the Zn content is greater than 0%, Zn will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated Zn inhibits the formation of precipitates at the grain boundaries, or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as Zn is contained in a small amount, the above effect can be achieved to a certain extent.
[0222] However, if the Zn content is greater than 0.0100%, Zn will be excessively segregated at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. At this time, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, it will promote grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment.
[0223] Therefore, the Zn content is greater than 0 and is 0.0100% or less.
[0224] The lower limit of the Zn content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%.
[0225] The upper limit of the Zn content is preferably 0.0095%, more preferably 0.0090%, and further preferably 0.0080%.
[0226] The preferred range of the Zn content is, for example, 0.0001 to 0.0095%, more preferably 0.0010 to 0.0090%, and even more preferably 0.0020 to 0.0080%.
[0227] Pb: more than 0 and less than 0.0100%
[0228] Lead (Pb) may not be contained. That is, the Pb content may be 0%.
[0229] When this element is contained, that is, when the Pb content is greater than 0%, Pb will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated Pb inhibits the formation of precipitates at the grain boundaries, or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as Pb is contained in a small amount, the above effect can be achieved to a certain extent.
[0230] However, if the Pb content is greater than 0.0100%, Pb will excessively segregate at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. At this time, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, it will promote grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment.
[0231] Therefore, the Pb content is greater than 0 and is 0.0100% or less.
[0232] The lower limit of the Pb content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%.
[0233] The upper limit of the Pb content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0234] The preferred range of the Pb content is, for example, 0.0001 to 0.0090%, more preferably 0.0010 to 0.0080%, and even more preferably 0.0020 to 0.0070%.
[0235] Sb: more than 0 and less than 0.0100%
[0236] Antimony (Sb) may not be contained. That is, the Sb content may be 0%.
[0237] When this element is contained, that is, when the Sb content is greater than 0%, Sb will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated Sb inhibits the formation of precipitates at the grain boundaries, or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as Sb is contained in a small amount, the above effect can be achieved to a certain extent.
[0238] However, if the Sb content is greater than 0.0100%, Sb will be excessively segregated at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. In this case, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment will be promoted.
[0239] Therefore, the Sb content is greater than 0 and is 0.0100% or less.
[0240] The lower limit of the Sb content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0015%.
[0241] The upper limit of the Sb content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0242] The Sb content is preferably in the range of, for example, 0.0001 to 0.0090%, more preferably 0.0010 to 0.0080%, and even more preferably 0.0015 to 0.0070%.
[0243] As: greater than 0 and less than 0.0010%
[0244] Arsenic (As) may not be contained. That is, the As content may be 0%.
[0245] When this element is contained, that is, when the As content is greater than 0%, As will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated As inhibits the formation of precipitates at the grain boundaries, or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as a small amount of As is contained, the above effect can be achieved to a certain extent.
[0246] However, if the As content is greater than 0.0010%, As will be excessively segregated at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. At this time, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, it will promote grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment.
[0247] Therefore, the As content is greater than 0 and is 0.0010% or less.
[0248] The lower limit of the As content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003%.
[0249] The upper limit of the As content is preferably 0.0009%, more preferably 0.0008%, and further preferably 0.0007%.
[0250] The As content is preferably in the range of, for example, 0.0001 to 0.0009%, more preferably 0.0002 to 0.0008%, and even more preferably 0.0003 to 0.0007%.
[0251] Bi: greater than 0 and less than 0.0010%
[0252] Bismuth (Bi) may not be contained. That is, the Bi content may be 0%.
[0253] When this element is contained, that is, when the Bi content is greater than 0%, Bi will segregate at the grain boundaries during the use of the alloy material in a high-temperature ammonia environment. The segregated Bi inhibits the formation of precipitates at the grain boundaries or the segregation of P and S at the grain boundaries. As a result, the grain boundaries can be strengthened and the grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment can be inhibited. As long as Bi is contained in a small amount, the above effect can be achieved to a certain extent.
[0254] However, if the Bi content is greater than 0.0010%, Bi will be excessively segregated at the grain boundaries during use of the alloy material in a high-temperature ammonia environment. At this time, the strength of the grain boundaries will be reduced. Therefore, even if the content of other elements is within the range of this embodiment, it will promote grain boundary cracks near the surface of the alloy material in a high-temperature ammonia environment.
[0255] Therefore, the Bi content is greater than 0 and is 0.0010% or less.
[0256] The lower limit of the Bi content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003%.
[0257] The upper limit of the Bi content is preferably 0.0009%, more preferably 0.0008%, and further preferably 0.0007%.
[0258] The preferred range of the Bi content is, for example, 0.0001 to 0.0009%, more preferably 0.0002 to 0.0008%, and even more preferably 0.0003 to 0.0007%.
[0259] The austenitic alloy material according to the present embodiment further contains one or more selected from the group consisting of the second group to the fourth group.
[0260] [Group 2]
[0261] Freedom to choose
[0262] Cu: more than 0 and less than 5.00%, and
[0263] Mo: one or more selected from the group consisting of more than 0 and 20.00% or less
[0264] [Group 3]
[0265] Freedom to choose
[0266] Co: more than 0 and 3.00% or less,
[0267] W: greater than 0 and less than 7.00%,
[0268] Ti: more than 0 and less than 1.00%,
[0269] Nb: more than 0 and less than 0.10%,
[0270] V: greater than 0 and less than 0.50%,
[0271] B: greater than 0 and less than 0.0050%,
[0272] N: greater than 0 and less than 0.200%, and
[0273] Rare earth elements: one or more selected from the group consisting of more than 0 and less than 0.100%
[0274] [Group 4]
[0275] Freedom to choose
[0276] Al: more than 0 and 0.500% or less,
[0277] Ca: more than 0 and 0.0100% or less, and
[0278] Mg: one or more selected from the group consisting of more than 0 and 0.0150% or less
[0279] Hereinafter, each element of the second group to the fourth group will be described.
[0280] [(Group 2) Cu and Mo]
[0281] Both Cu and Mo improve the nitridation resistance of the alloy material in a high-temperature ammonia environment. Each element is described below.
[0282] Cu: more than 0 and less than 5.00%
[0283] Copper (Cu) may not be contained. That is, the Cu content may be 0%.
[0284] When this element is contained, that is, when the Cu content is greater than 0%, Cu improves the nitriding resistance of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as Cu is contained in a small amount.
[0285] However, if the Cu content exceeds 5.00%, the creep ductility of the alloy material in a high-temperature ammonia environment decreases even if the contents of other elements are within the ranges of the present embodiment.
[0286] Therefore, the Cu content is greater than 0 and is 5.00% or less.
[0287] The lower limit of the Cu content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.50%, more preferably 1.00%, and still more preferably 1.50%.
[0288] The upper limit of the Cu content is preferably 4.50%, more preferably 4.00%, more preferably 3.50%, more preferably 3.00%, and more preferably 2.50%.
[0289] The preferred range of the Cu content is, for example, 0.01 to 4.50%, more preferably 0.05 to 4.00%, more preferably 0.10 to 3.50%, more preferably 0.50 to 3.00%, more preferably 1.00 to 2.50%, and more preferably 1.50 to 2.50%.
[0290] Mo: more than 0 and less than 20.00%
[0291] Molybdenum (Mo) may not be contained. That is, the Mo content may be 0%.
[0292] When this element is contained, that is, when the Mo content is greater than 0%, Mo improves the nitriding resistance of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as Mo is contained in a small amount.
[0293] However, if the Mo content exceeds 20.00%, the hot workability of the alloy material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0294] Therefore, the Mo content is greater than 0 and is 20.00% or less.
[0295] The lower limit of the Mo content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.50%, more preferably 1.00%, more preferably 1.50%, more preferably 3.00%, more preferably 5.00%, and more preferably 8.00%.
[0296] The upper limit of the Mo content is preferably 18.00%, more preferably 16.00%, and further preferably 14.00%.
[0297] The preferred range of the Mo content is, for example, 0.01 to 18.00%, more preferably 0.05 to 16.00%, more preferably 0.10 to 14.00%, more preferably 0.50 to 14.00%, more preferably 1.00 to 14.00%, more preferably 1.50 to 14.00%, more preferably 3.00 to 14.00%, more preferably 5.00 to 14.00%, and more preferably 8.00 to 14.00%.
[0298] [(Group 3) Co, W, Ti, Nb, V, B, N and rare earth elements]
[0299] Co, W, Ti, Nb, V, B, N and rare earth elements (REM) all increase the creep strength of alloy materials in a high-temperature ammonia environment. Each element is described below.
[0300] Co: more than 0 and less than 3.00%
[0301] Cobalt (Co) may not be contained. That is, the Co content may be 0%.
[0302] When this element is contained, that is, when the Co content is greater than 0%, Co dissolves in the alloy material and improves the creep strength of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as Co is contained in a small amount.
[0303] However, if the Co content exceeds 3.00%, the effect is saturated and the manufacturing cost becomes high.
[0304] Therefore, the Co content is greater than 0 and is 3.00% or less.
[0305] The lower limit of the Co content is preferably 0.01%, more preferably 0.05%, further preferably 0.10%, further preferably 0.15%.
[0306] The upper limit of the Co content is preferably 2.80%, more preferably 2.50%, and further preferably 2.00%.
[0307] The Co content is preferably in the range of, for example, 0.01 to 2.80%, more preferably 0.05 to 2.50%, further preferably 0.10 to 2.00%, and further preferably 0.15 to 2.00%.
[0308] W: greater than 0 and less than 7.00%
[0309] Tungsten (W) may not be contained. That is, the W content may be 0%.
[0310] When the element is contained, that is, when the W content is greater than 0%, W is dissolved in the alloy material, and the creep strength of the alloy material in a high-temperature ammonia environment is improved. W further generates precipitates during the use of the alloy material in a high-temperature ammonia environment, and the creep strength of the alloy material in a high-temperature ammonia environment is improved. As long as W is contained in a small amount, the above effect can be achieved to a certain extent.
[0311] However, if the W content exceeds 7.00%, the hot workability of the alloy material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0312] Therefore, the W content is greater than 0 and is 7.00% or less.
[0313] The lower limit of the W content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.50%, more preferably 1.00%, and more preferably 2.00%.
[0314] The upper limit of the W content is preferably 6.50%, more preferably 6.00%, more preferably 5.50%, more preferably 5.00%, more preferably 4.50%, more preferably 4.00%, and more preferably 3.50%.
[0315] The preferred range of the W content is, for example, 0.01 to 6.50%, more preferably 0.05 to 6.00%, more preferably 0.10 to 5.50%, more preferably 0.50 to 5.00%, more preferably 1.00 to 4.50%, more preferably 2.00 to 4.00%, and more preferably 2.00 to 3.50%.
[0316] Ti: more than 0 and less than 1.00%
[0317] Titanium (Ti) may not be contained. That is, the Ti content may be 0%.
[0318] When the element is contained, that is, when the Ti content is greater than 0%, Ti forms precipitates during the use of the alloy material in a high-temperature ammonia environment, thereby improving the creep strength of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as a small amount of Ti is contained.
[0319] However, if the Ti content exceeds 1.00%, even if the contents of other elements are within the range of the present embodiment, Ti precipitates will become coarse, and in this case, the creep strength and toughness of the alloy material will decrease.
[0320] Therefore, the Ti content is greater than 0 and is 1.00% or less.
[0321] The lower limit of the Ti content is preferably 0.01%, more preferably 0.02%, further preferably 0.05%, further preferably 0.10%.
[0322] The upper limit of the Ti content is preferably 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.60%, more preferably 0.50%, more preferably 0.45%, more preferably 0.40%, more preferably 0.35%, and more preferably 0.30%.
[0323] The preferred range of Ti content is, for example, 0.01 to 0.90%, more preferably 0.02 to 0.80%, more preferably 0.05 to 0.70%, more preferably 0.10 to 0.60%, more preferably 0.10 to 0.50%, more preferably 0.10 to 0.45%, more preferably 0.10 to 0.40%, more preferably 0.10 to 0.35%, and more preferably 0.10 to 0.30%.
[0324] Nb: more than 0 and less than 0.10%
[0325] Niobium (Nb) may not be contained. That is, the Nb content may be 0%.
[0326] When the element is contained, that is, when the Nb content is greater than 0%, Nb forms precipitates during the use of the alloy material in a high-temperature ammonia environment, thereby improving the creep strength of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as Nb is contained in a small amount.
[0327] However, when the Nb content exceeds 0.10%, Nb precipitates become coarse and in this case, even if the contents of other elements are within the range of the present embodiment, the creep strength and toughness of the alloy material decrease.
[0328] Therefore, the Nb content is greater than 0 and is 0.10% or less.
[0329] The lower limit of the Nb content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%.
[0330] The upper limit of the Nb content is preferably 0.09%, more preferably 0.08%, and further preferably 0.07%.
[0331] The preferred range of the Nb content is, for example, 0.01 to 0.09%, more preferably 0.02 to 0.08%, and even more preferably 0.03 to 0.07%.
[0332] V: greater than 0 and less than 0.50%
[0333] Vanadium (V) may not be contained. That is, the V content may be 0%.
[0334] When the element is contained, that is, when the V content is greater than 0%, V forms precipitates during the use of the alloy material in a high-temperature ammonia environment, thereby improving the creep strength of the alloy material in a high-temperature ammonia environment. The above effect can be achieved to a certain extent as long as V is contained in a small amount.
[0335] However, if the V content exceeds 0.50%, V precipitates will become coarse. In this case, even if the contents of other elements are within the range of the present embodiment, the creep strength and toughness of the alloy material will decrease.
[0336] Therefore, the V content is greater than 0 and is 0.50 or less.
[0337] The lower limit of the V content is preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.
[0338] The upper limit of the V content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.
[0339] The preferred range of the V content is, for example, 0.01 to 0.45%, more preferably 0.05 to 0.40%, and even more preferably 0.10 to 0.35%.
[0340] B: greater than 0 and less than 0.0050%
[0341] Boron (B) may not be contained. That is, the B content may be 0%.
[0342] When this element is contained, that is, when the B content is greater than 0%, B will segregate at the grain boundaries in a high-temperature ammonia environment and strengthen the grain boundaries. Therefore, the creep strength of the alloy material in a high-temperature ammonia environment is improved. As long as B is contained in a small amount, the above effect can be achieved to a certain extent.
[0343] However, if the B content exceeds 0.0050%, the hot workability and weldability of the alloy material will be reduced even if the contents of other elements are within the ranges of the present embodiment.
[0344] Therefore, the B content is greater than 0 and is 0.0050% or less.
[0345] The lower limit of the B content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0005%.
[0346] The upper limit of the B content is preferably 0.0045%, more preferably 0.0040%, and further preferably 0.0035%.
[0347] The preferred range of the B content is, for example, 0.0001 to 0.0045%, more preferably 0.0002 to 0.0040%, and even more preferably 0.0005 to 0.0035%.
[0348] N: greater than 0 and less than 0.200%
[0349] Nitrogen (N) may not be contained. In other words, it may not be contained. In other words, the N content may be 0%.
[0350] When this element is contained, that is, when the N content is greater than 0%, N is dissolved in the alloy material, improving the creep strength of the alloy material in a high-temperature ammonia environment. N further forms precipitates during the use of the alloy material in a high-temperature ammonia environment, improving the creep strength of the alloy material in a high-temperature ammonia environment. As long as N is contained in a small amount, the above effect can be achieved to a certain extent.
[0351] However, if the N content exceeds 0.200%, even if the contents of other elements are within the range of the present embodiment, excessive nitrides will be generated during use of the alloy material in a high-temperature ammonia environment, and the creep ductility or toughness of the alloy material will be reduced.
[0352] Therefore, the N content is greater than 0 and is 0.200% or less.
[0353] The lower limit of the N content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%.
[0354] The upper limit of the N content is preferably 0.190%, more preferably 0.160%, further preferably 0.140%, further preferably 0.120%.
[0355] The preferred range of the N content is, for example, 0.001 to 0.190%, more preferably 0.005 to 0.160%, further preferably 0.010 to 0.140%, and further preferably 0.010 to 0.120%.
[0356] Rare earth elements: greater than 0 and less than 0.100%
[0357] Rare earth elements (REM) may not be contained. That is, the REM content may be 0%.
[0358] When this element is contained, that is, when the REM content is greater than 0%, REM will segregate at the grain boundaries in a high-temperature ammonia environment and strengthen the grain boundaries. Therefore, the creep strength of the alloy material in a high-temperature ammonia environment is improved. The above effect can be achieved to a certain extent as long as REM is contained in a small amount.
[0359] However, if the REM content exceeds 0.100%, inclusions such as oxides are formed in the alloy material. Therefore, even if the contents of other elements are within the range of the present embodiment, the creep strength of the alloy material is reduced.
[0360] Therefore, the REM content is greater than 0 and is 0.100% or less.
[0361] The lower limit of the REM content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%.
[0362] The upper limit of the REM content is preferably 0.090%, more preferably 0.070%, and further preferably 0.055%.
[0363] The REM content is preferably in the range of, for example, 0.001 to 0.090%, more preferably 0.005 to 0.070%, and even more preferably 0.010 to 0.055%.
[0364] In the present specification, REM contains one or more elements selected from the group consisting of Sc, Y, and lanthanides (La with atomic number 57 to Lu with atomic number 71), and the REM content means the total content (mass %) of these elements.
[0365] [(Group 4) Al, Ca and Mg]
[0366] Al, Ca, and Mg all deoxidize the alloy in the process of manufacturing the alloy material. Hereinafter, each element will be described.
[0367] Al: more than 0 and 0.500% or less
[0368] Aluminum (Al) may not be contained. That is, the Al content may be 0%.
[0369] When this element is contained, that is, when the Al content is greater than 0%, Al deoxidizes the alloy in the production process of the alloy material. The above-mentioned effect can be obtained to a certain extent as long as Al is contained in a small amount.
[0370] However, if the Al content exceeds 0.500%, even if the contents of other elements are within the ranges of the present embodiment, excessive inclusions are generated, thereby reducing the creep strength and toughness of the alloy material.
[0371] Therefore, the Al content is greater than 0 and is 0.500% or less.
[0372] The lower limit of the Al content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%.
[0373] The upper limit of the Al content is preferably 0.450%, more preferably 0.400%, further preferably 0.350%, further preferably 0.300%.
[0374] The preferred range of the Al content is, for example, 0.001 to 0.450%, more preferably 0.005 to 0.400%, further preferably 0.010 to 0.350%, and further preferably 0.010 to 0.300%.
[0375] Ca: more than 0 and less than 0.0100%
[0376] Calcium (Ca) may not be contained. That is, the Ca content may be 0%.
[0377] When this element is contained, that is, when the Ca content is greater than 0%, Ca deoxidizes the alloy in the production process of the alloy material. The above-mentioned effect can be obtained to a certain extent as long as Ca is contained in a small amount.
[0378] However, if the Ca content exceeds 0.0100%, even if the contents of other elements are within the ranges of the present embodiment, excessive inclusions are generated, thereby reducing the creep strength and toughness of the alloy material.
[0379] Therefore, the Ca content is greater than 0 and is 0.0100% or less.
[0380] The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%.
[0381] The upper limit of the Ca content is preferably 0.0090%, more preferably 0.0080%, further preferably 0.0070%, further preferably 0.0060%.
[0382] The preferred range of the Ca content is, for example, 0.0001 to 0.0090%, more preferably 0.0005 to 0.0080%, further preferably 0.0010 to 0.0070%, and further preferably 0.0010 to 0.0060%.
[0383] Mg: more than 0 and less than 0.0150%
[0384] Magnesium (Mg) may not be contained. That is, the Mg content may be 0%.
[0385] When this element is contained, that is, when the Mg content is greater than 0%, Mg deoxidizes the alloy in the manufacturing process of the alloy material. The above-mentioned effect can be obtained to a certain extent as long as Mg is contained in a small amount.
[0386] However, if the Mg content exceeds 0.0150%, even if the contents of other elements are within the ranges of the present embodiment, excessive inclusions are generated, thereby reducing the creep strength and toughness of the alloy material.
[0387] Therefore, the Mg content is greater than 0 and is 0.0150% or less.
[0388] The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%.
[0389] The upper limit of the Mg content is preferably 0.0140%, more preferably 0.0120%, further preferably 0.0100%, further preferably 0.0080%.
[0390] The preferred range of the Mg content is, for example, 0.0001 to 0.0140%, more preferably 0.0005 to 0.0120%, further preferably 0.0010 to 0.0100%, and further preferably 0.0010 to 0.0080%.
[0391] The balance of the chemical composition of the austenitic alloy material according to the present embodiment is Fe and impurities. Here, the impurities in the chemical composition refer to substances that are mixed from ores, waste materials or manufacturing environments as raw materials when the austenitic alloy material is manufactured industrially, are not intentionally contained, and are allowed within a range that does not adversely affect the austenitic alloy material of the present embodiment.
[0392] The Fe content is preferably greater than 0 and less than 30.00%. Specifically, Fe improves the hot workability of Ni-based alloys. When the Fe content is too low, the above effect cannot be fully obtained. On the other hand, when the Fe content is too high, the corrosion resistance of the Ni-based alloy will decrease. Therefore, the Fe content is preferably greater than 0 and less than 30.00%.
[0393] The lower limit of the Fe content is preferably 0.01%, more preferably 0.20%, further preferably 0.40%, further preferably 0.50%.
[0394] The upper limit of the Fe content is preferably 29.00%, more preferably 27.00%, further preferably 25.00%, further preferably 23.00%.
[0395] The Fe content is preferably in the range of 0.01 to 29.00%, for example, more preferably 0.20 to 27.00%, further preferably 0.40 to 25.00%, and further preferably 0.50 to 23.00%.
[0396] [About the Preferred Chemical Composition of Austenitic Alloy Material]
[0397] The chemical composition of the austenitic alloy material according to the present embodiment is preferably any one of the following first to third chemical compositions.
[0398] (1st chemical composition)
[0399] It is a chemical composition that satisfies feature 1, and the chemical composition contains C: less than 0.050%, Si: 0.01-0.50%, Mn: 0.01-0.50%, P: less than 0.025%, S: less than 0.010%, Cu: 2.00-4.00%, Ni: 44.00-50.00%, Cr: 20.00-25.00%, Mo: 5.00-7.00%, W: 2.00-5.00%, and Fe: 12.00-20.00%.
[0400] (Second chemical composition)
[0401] It is a chemical composition that satisfies feature 1, and the chemical composition contains C: less than 0.150%, Si: 1.00-2.50%, Mn: 0.01-1.00%, P: less than 0.010%, S: less than 0.010%, Cu: 1.50-3.00%, Cr: 28.00-32.00%, Mo: 1.00-3.00%, Ti: 0.01-1.00%, and Fe: 2.00-6.00%.
[0402] (Chemical composition No. 3)
[0403] It is a chemical composition that satisfies feature 1, and the chemical composition contains C: less than 0.050%, Si: 0.01-0.50%, Mn: 0.01-0.50%, P: less than 0.030%, S: less than 0.015%, Cu: 0.01-0.50%, Cr: 27.00-31.00%, Fe: 7.00-15.00%, and Ni: 58.00-80.00%.
[0404] [About (Feature 2) Fn1]
[0405] In the austenitic alloy material of the present embodiment, Fn1 defined by the formula (1) is smaller than 20.
[0406] Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1)
[0407] The element symbol in formula (1) is replaced by the content of the corresponding element in mass %. If the element is not contained, "0" is replaced by the corresponding element symbol.
[0408] Fn1 is an index related to the nitriding resistance of the alloy material in a high-temperature ammonia environment. Among the elements in the above chemical composition, Mn, Cu, Cr, Ni and Mo improve the nitriding resistance of the austenitic alloy material in a high-temperature ammonia environment. Si reduces the nitriding resistance of the austenitic alloy material in a high-temperature ammonia environment. Figure 1 As shown in FIG. 1 , if Fn1 is less than 20, the depth of the nitrided layer is less than 15.0 μm when kept at 600° C. for 25 hours in a 100% ammonia atmosphere. Therefore, if Fn1 is less than 20, excellent nitriding resistance can be obtained in the austenitic alloy material used in a high-temperature ammonia environment.
[0409] The preferred upper limit of Fn1 is 19, more preferably 18, more preferably 17, more preferably 16, more preferably 13, and more preferably 10. When Fn1 is 10 or less, the depth of the nitrided layer can be significantly reduced, and more excellent nitriding resistance can be obtained.
[0410] The lower limit of Fn1 is not particularly limited. The lower limit of Fn1 is 1, for example, or 2, for example.
[0411] The preferred range of Fn1 is, for example, 1 to 19, more preferably 2 to 18, more preferably 2 to 17, more preferably 2 to 16, more preferably 2 to 13, and even more preferably 2 to 10.
[0412] It should be noted that the Fn1 value is an integer, that is, the Fn1 value is an integer obtained by rounding off the first decimal point of the obtained value.
[0413] [About (Feature 3) Fn2]
[0414] In the austenitic alloy material of the present embodiment, Fn2 defined by the formula (2) is greater than 21 and less than 50.
[0415] Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2)
[0416] The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
[0417] Fn2 is an index related to the grain boundary cracks in the surface layer of the alloy material under a high-temperature ammonia environment. If Fn2 is less than 21, even if the alloy material satisfies characteristics 1 and 2, grain boundary cracks are likely to occur in the surface layer of the alloy material under a high-temperature ammonia environment. On the other hand, if Fn2 is more than 50, Sn, Zn, Pb, Sb, As and Bi are excessively segregated at the grain boundaries, and the grain boundary strength is reduced. Therefore, even if the alloy material satisfies characteristics 1 and 2, grain boundary cracks are likely to occur in the surface layer of the alloy material under a high-temperature ammonia environment.
[0418] If Fn2 is greater than 21 and less than 50, the occurrence of grain boundary cracks can be sufficiently suppressed in the surface layer of the alloy material in a high-temperature ammonia environment, provided that the alloy material satisfies characteristics 1 and 2.
[0419] The preferred lower limit of Fn2 is 22, more preferably 24, and even more preferably 26.
[0420] The upper limit of Fn2 is preferably 48, more preferably 46, and even more preferably 44.
[0421] The preferred range of Fn2 is, for example, 22-48, more preferably 24-46, and even more preferably 26-44.
[0422] It should be noted that the Fn2 value is an integer, that is, the Fn2 value is an integer obtained by rounding off the first decimal point of the obtained value.
[0423] [Effects of the Austenitic Alloy Material of the Present Embodiment]
[0424] As described above, the austenitic alloy material of the present embodiment satisfies Characteristics 1 to 3. Therefore, the austenitic alloy material of the present embodiment can obtain excellent nitridation resistance and can sufficiently suppress the occurrence of grain boundary cracks in the surface layer during use in a high-temperature ammonia environment.
[0425] [Shape and use]
[0426] The shape of the austenitic alloy material of the present embodiment is not particularly limited. The austenitic alloy material of the present embodiment may be an alloy tube, a rod-shaped solid material, or an alloy plate. In addition, the alloy tube may be a seamless tube or a welded tube.
[0427] The austenitic alloy material of this embodiment can be widely used in applications requiring nitriding resistance. In particular, the austenitic alloy material of this embodiment is suitable for high-temperature ammonia environments. However, the austenitic alloy material of this embodiment can also be used for other applications other than high-temperature ammonia environments.
[0428] [Preferred Modes of the Austenitic Alloy Material of the Present Embodiment]
[0429] The austenitic alloy material of the present embodiment preferably satisfies Characteristics 1 to 3, and further satisfies the following Characteristics 4.
[0430] (Feature 4)
[0431] The average grain size in μm of the surface layer of the austenitic alloy material is defined as D ave hour,
[0432] Fn3 defined by formula (3) is greater than 0.20,
[0433] Fn4 defined by formula (4) is 1000 to 5000.
[0434] Fn3=Fn2 / D ave (3)
[0435] Fn4=Fn2×D ave (4)
[0436] Feature 4 will be described below.
[0437] Fn3 and Fn4 are indices related to the grain boundary cracks in the surface layer of the alloy material under a high-temperature ammonia environment.
[0438] The total content of Sn, Zn, Pb, Sb, As and Bi (i.e. Fn2) and the average grain size D of the alloy material ave When (μm) satisfies an appropriate relationship, grain boundary cracking in a high-temperature ammonia environment can be further suppressed. Next, Fn3 and Fn4 are described.
[0439] [About Fn3]
[0440] When Fn2 satisfies formula (2), if Fn3 is greater than 0.20, the total content of Sn, Zn, Pb, Sb, As and Bi per unit grain boundary area is more appropriate. Therefore, grain boundary cracking in a high-temperature ammonia environment can be further suppressed.
[0441] Therefore, it is preferred that Fn3 is greater than 0.20.
[0442] The lower limit of Fn3 is preferably 0.21, more preferably 0.22, and further preferably 0.23.
[0443] The upper limit of Fn3 is not particularly limited. However, when the austenitic alloy material satisfies characteristics 1 to 3, the upper limit of Fn3 is, for example, preferably 0.90, more preferably 0.85, and even more preferably 0.82.
[0444] The preferred range of Fn3 is, for example, 0.21 to 0.90, more preferably 0.22 to 0.85, and even more preferably 0.23 to 0.82.
[0445] It should be noted that the Fn3 value is a value obtained by rounding off the third decimal place of the obtained value to the second decimal place.
[0446] [About Fn4]
[0447] Furthermore, when Fn2 satisfies formula (2), if Fn4 is 1000 to 5000, the grain boundary area is appropriate, and the total content of Sn, Zn, Pb, Sb, As and Bi is also appropriate. In this case, not only the generation of cracks can be more effectively suppressed, but also the expansion of cracks can be more effectively suppressed. As a result, grain boundary cracks in a high-temperature ammonia environment can be further suppressed.
[0448] Therefore, Fn4 is preferably 1,000 to 5,000.
[0449] The lower limit of Fn4 is preferably 1100, more preferably 1200.
[0450] The upper limit of Fn4 is preferably 4,900, more preferably 4,600, and even more preferably 4,200.
[0451] The preferred range of Fn4 is, for example, 1100 to 4900, more preferably 1200 to 4600, and even more preferably 1200 to 4200.
[0452] It should be noted that the value of Fn4 is an integer.
[0453] [Method for measuring the average grain size of the surface layer of an austenitic alloy material]
[0454] The average grain size D of the surface layer of austenitic alloy materials ave It was measured by the following method.
[0455] The test piece is cut from the cross section (L cross section) parallel to the rolling direction of the austenitic alloy material. The test piece has a rectangular observation surface consisting of a side of 5 mm in length corresponding to the surface of the alloy material and a side of 5 mm in depth direction from the surface. That is, the observation surface is a rectangle of 5 mm × 5 mm. The size of the test piece other than the observation surface is not particularly limited.
[0456] The test piece is embedded in a resin for microstructure observation. The observation surface of the test piece embedded in the resin is mirror-polished. The mirror-polished observation surface is etched using a mixed acid of hydrochloric acid and nitric acid to reveal the microstructure. Observe any 10 fields of view of the etched observation surface using a 300x optical microscope. Each field of view is 1000μm×1000μm. In each field of view, the grain diameter (μm) is calculated according to the cutting method described in JIS G 0551:2020. The arithmetic mean of the grain diameters of the 10 fields of view obtained is taken as the average grain diameter D of the surface layer of the austenitic alloy material. ave (μm).
[0457] [Method for producing austenitic alloy material according to present embodiment]
[0458] An example of a method for producing an austenitic alloy material according to the present embodiment will be described. An example of a method for producing an austenitic alloy material according to the present embodiment includes a billet preparation step, a hot working step, and a solution treatment step. Each step will be described in detail.
[0459] [Blank material preparation process]
[0460] In the billet preparation process, the alloy satisfying characteristics 1 to 3 or characteristics 1 to 4 is melted. The alloy can be melted in an electric furnace, or in an Ar-O2 mixed gas bottom blowing decarburization furnace (AOD furnace), or in a vacuum decarburization furnace (VOD furnace). The smelted alloy can be made into ingots by an ingot casting method, or can be made into slabs, blooms or billets by a continuous casting method. As needed, the slabs, blooms or ingots can be opened and rolled to produce billets. Billets (slabs, blooms or billets) are manufactured through the above process.
[0461] [Hot working process]
[0462] In the hot working step, the produced billet is subjected to known hot working to produce an intermediate alloy material. The hot working may be hot forging, hot extrusion, or hot rolling. The hot working method is not particularly limited and may be a known method.
[0463] When the final product is an alloy tube, for example, the Mannesmann process can be implemented as a hot working to produce a tube blank as an intermediate alloy material. In addition, the glass lubricant high-speed extrusion method (Ugine-Sejournet process) or the Ehrhardt push bench method (i.e., hot extrusion) can also be implemented as a hot working to produce a tube blank. In addition, the produced tube blank can also be subjected to hot rolling using a mandrel mill, a reducing mill, a sizing mill, etc.
[0464] [Solution treatment process]
[0465] In the solution treatment step, the intermediate alloy material produced by the hot working step is subjected to a known solution treatment. For example, the intermediate alloy material is placed in a heat treatment furnace, maintained at a desired temperature, and then rapidly cooled. The solution treatment temperature is, for example, 1000 to 1300°C.
[0466] It should be noted that the grain size can be adjusted by adjusting the reduction ratio in the hot working step and the solution treatment temperature in the solution treatment step. The austenitic alloy material of the present embodiment can be manufactured by the above-mentioned manufacturing method.
[0467] [About other processes]
[0468] The manufacturing method of the austenitic alloy material of the present embodiment may also include processes other than the above-mentioned processes. For example, a cold working process may be implemented to the intermediate alloy material after the hot working process and before the solution treatment process. In the cold working process, the intermediate alloy material is cold worked. The cold working may be cold rolling or cold drawing. At this time, it may be processed into a desired size. For example, the intermediate alloy material after the solution treatment process may also be cold worked. At this time, the strength of the austenitic alloy material may be improved.
[0469] It should be noted that in the above-mentioned manufacturing method, the manufacturing method of the alloy tube as an example of the austenitic alloy material is described. However, the austenitic alloy material of the present embodiment may also be in other shapes such as rods or plates. Similar to the above-mentioned manufacturing method, the rod-shaped or plate-shaped manufacturing method also has, for example, a blank preparation process, a hot working process, and a solution treatment process, and further, a cold working process may also be implemented. Furthermore, the above-mentioned manufacturing method is only an example, and the austenitic alloy material of the present embodiment that satisfies features 1 to 3 or features 1 to 4 may also be manufactured by other manufacturing methods.
[0470] Example
[0471] The effect of the austenitic alloy material of the present embodiment will be described in more detail by way of examples. The conditions in the following examples are an example of conditions used to confirm the feasibility and effect of the austenitic alloy material of the present embodiment. Therefore, the austenitic alloy material of the present embodiment is not limited to this one example of conditions.
[0472] Austenitic alloy materials having the chemical compositions shown in Table 1 (Table 1-1 and Table 1-2) were produced. It should be noted that "-" in Table 1 means that the corresponding element content is below the impurity level.
[0473] [Table 1-1]
[0474] Table 1-1
[0475]
[0476] [Table 1-2]
[0477] Table 1-2
[0478]
[0479] The alloy of each test number is melted by high-frequency vacuum melting method. Using the molten alloy, a 30kg ingot is manufactured by the ingot casting method. The ingot of each test number is heated at 1200°C for 2 hours. The heated ingot is hot forged to manufacture a square material with a cross-section of 50mm×55mm. After heating the obtained square material at 1200°C for 30 minutes, it is hot rolled to manufacture a hot-rolled material with a plate thickness of 15mm. The obtained hot-rolled material is cold rolled to manufacture an intermediate alloy material (alloy plate) with a plate thickness of 10.5mm. The intermediate alloy material is subjected to a solution treatment at a solution treatment temperature of 1150°C for 10 minutes. It should be noted that water cooling is used as the cooling method after maintaining at the solution treatment temperature. Through the above-mentioned manufacturing process, the austenitic alloy material (alloy plate) of each test number is manufactured.
[0480] [Evaluation test]
[0481] The following evaluation tests were performed on the manufactured austenitic alloy materials of each test number.
[0482] [Nitriding resistance and surface grain boundary crack evaluation test]
[0483] The nitriding resistance and surface grain boundary cracking of the austenitic alloy material of each test number were evaluated by the following method.
[0484] A test piece with a thickness of 3 mm, a width of 15 mm, and a length of 20 mm was cut out from the austenitic alloy material (alloy plate) of each test number. The surface of the test piece was polished and then degreased. The degreased test piece was hung on a quartz fixture using a stainless steel wire and loaded into a box furnace. While the atmosphere gas was passed into the furnace after the test piece was loaded, it was kept at 600°C for 25 hours. The atmosphere gas was 100% ammonia. The flow rate of the atmosphere gas was 500 mL / min.
[0485] A test piece for tissue observation is prepared, which includes a cross section perpendicular to the length direction of the test piece after 25 hours and the surface of the test piece. In the test piece for tissue observation, the above cross section is used as the observation surface. A scanning electron microscope (SEM) is used to observe a rectangular field of view containing the surface of the test piece on the observation surface at a magnification of 300 times, and a depth of 600μm from the surface and 800μm in the width direction to obtain a photographic image (reflected electron image). Furthermore, in the rectangular field of view, an EDS analysis is performed using an EDS device attached to the SEM device. Specifically, EDS analysis is performed in the depth direction from any point of the rectangular field of view corresponding to the surface of the test piece. The area in the analysis result that is more than twice the N content (mass %) compared to the N content (mass %) of the base material is identified as a nitride layer. The depth of the area identified as the nitride layer from the surface of the test piece is defined as the nitride layer depth (μm). The obtained nitride layer depth is shown in the "nitride layer depth (μm)" column in Table 2.
[0486] Furthermore, the presence or absence of grain boundary cracks is confirmed in the surface layer of the test piece in the photographic image of the rectangular field of view of each test number. In the case where there is no area with a confirmed length of pores of 0.5 μm or more on the grain boundary, it is judged that the grain boundary cracks are fully suppressed (marked as "E" (Excellent) in "Grain Boundary Cracks" in Table 2). In the case where there is an area with a confirmed length of pores of 0.5 μm or more on the grain boundary, but there is no area with a confirmed length of pores of 1.0 μm or more, it is judged that the grain boundary cracks are suppressed (marked as "G" (Good) in "Grain Boundary Cracks" in Table 2). In the case where there is an area with a confirmed length of pores of 1 μm or more on the grain boundary, it is judged that the grain boundary cracks are not fully suppressed (marked as "B" (Bad) in "Grain Boundary Cracks" in Table 2). It should be noted that the length of the pores refers to the total length of the pores along the grain boundaries.
[0487] [Table 2]
[0488] Table 2
[0489]
[0490] [Test results]
[0491] The test results are shown in Table 1 (Table 1-1, Table 1-2) and Table 2. As shown in each table, the austenitic alloy materials of test numbers 1 to 43 satisfy characteristics 1 to 3. Therefore, the nitrided layer depth is 15.0 μm or less, and sufficient nitriding resistance is obtained in a high-temperature ammonia environment. Furthermore, grain boundary cracking is suppressed in a high-temperature ammonia environment.
[0492] In particular, the austenitic alloy materials of Test Nos. 1 to 18 and Test Nos. 25 to 43 satisfy not only Characteristics 1 to 3 but also Characteristics 4. Therefore, compared with Test Nos. 19 to 24 that do not satisfy Characteristics 4, grain boundary cracking is sufficiently suppressed.
[0493] On the other hand, in Test No. 44, the Si content was too high, so that the grain boundary cracks could not be sufficiently suppressed in the high-temperature ammonia environment.
[0494] In test number 45, the Ni content was too low. Therefore, in a high-temperature ammonia environment, the nitrided layer depth exceeded 15.0 μm, and sufficient nitriding resistance could not be obtained.
[0495] In test number 46, the Ni content was too high, so grain boundary cracking could not be sufficiently suppressed in a high-temperature ammonia environment.
[0496] In test number 47, the Cr content was too low. Therefore, in a high-temperature ammonia environment, the nitrided layer depth exceeded 15.0 μm, and sufficient nitriding resistance could not be obtained.
[0497] In test numbers 48 and 50, the Sb content was too high, and therefore, the grain boundary cracks could not be sufficiently suppressed in a high-temperature ammonia environment.
[0498] In Test No. 49, the Pb content was too high, so grain boundary cracking could not be sufficiently suppressed in a high-temperature ammonia environment.
[0499] In test numbers 51 to 53, Fn1 was too high. Therefore, in a high-temperature ammonia environment, the depth of the nitrided layer exceeded 15.0 μm, and sufficient nitridation resistance could not be obtained.
[0500] In test numbers 54 and 55, Fn2 was too high, and therefore, grain boundary cracking could not be sufficiently suppressed in a high-temperature ammonia environment.
[0501] In test numbers 56 to 58, Fn2 was too low, and therefore, grain boundary cracking could not be sufficiently suppressed in a high-temperature ammonia environment.
[0502] The embodiments of the present invention have been described above. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and the above embodiments may be appropriately modified to implement the present invention without departing from the scope of the present invention.
Claims
1. An austenitic alloy material, the chemical composition of which contains, by mass%, C: greater than 0 and less than 0.200%, Si: more than 0 and 3.00% or less, Mn: more than 0 and less than 3.00%, P: greater than 0 and less than 0.050%, S: greater than 0 and less than 0.050%, Ni: 40.00~80.00%, and Cr:10.00~35.00%, Also contains the freedom to choose Sn: greater than 0 and less than 0.1000%, Zn: more than 0 and less than 0.0100%, Pb: more than 0 and less than 0.0100%, Sb: more than 0 and less than 0.0100%, As: greater than 0 and less than 0.0010%, and Bi: one or more selected from the group consisting of more than 0 and 0.0010% or less, Further comprising Cu: more than 0 and less than 5.00%, Mo: more than 0 and less than 20.00%, Co: more than 0 and 3.00% or less, W: greater than 0 and less than 7.00%, Ti: more than 0 and less than 1.00%, Nb: more than 0 and less than 0.10%, V: greater than 0 and less than 0.50%, B: greater than 0 and less than 0.0050%, N: greater than 0 and less than 0.200%, Rare earth elements: greater than 0 and less than 0.100%, Al: more than 0 and 0.500% or less, Ca: more than 0 and 0.0100% or less, and Mg: one or more selected from the group consisting of more than 0 and 0.0150% or less, The balance is Fe and impurities. Fn1 defined by formula (1) is less than 20, Fn2 defined by formula (2) is greater than 21 and less than 50, Fn1=177.84+11.12Si-24.36Mn-8.11Cu-1.61Cr-1.78Ni-2.68Mo (1) Fn2=(Sn+Zn+Pb+Sb+As+Bi)×10 3 (2) in, The element symbol in the formula is substituted with the content of the corresponding element in mass %. If the element is not contained, "0" is substituted with the corresponding element symbol.
2. The austenitic alloy material according to claim 1, wherein: The average grain size in μm of the surface layer of the austenitic alloy material is defined as D ave hour, Fn3 defined by formula (3) is greater than 0.20, Fn4 defined by formula (4) is 1000 to 5000, Fn3=Fn2 / D ave (3) Fn4=Fn2×D ave (4).
3. The austenitic alloy material according to claim 1 or claim 2, wherein the chemical composition thereof contains, in mass %, C: greater than 0 and less than 0.050%, Si: more than 0 and less than 0.50%, Mn: more than 0 and less than 0.50%, P: greater than 0 and less than 0.025%, S: greater than 0 and less than 0.010%, Cu: 2.00~4.00%, Ni: 44.00~50.00%, Cr:20.00~25.00%、 Mo: 5.00~7.00%, W: 2.00~5.00%, and Fe: 12.00~20.00%.
4. The austenitic alloy material according to claim 1 or claim 2, wherein the chemical composition thereof contains, in mass %, C: greater than 0 and less than 0.150%, Si: 1.00~2.50%, Mn: more than 0 and less than 1.00%, P: greater than 0 and less than 0.010%, S: greater than 0 and less than 0.010%, Cu: 1.50-3.00%, Cr:28.00~32.00%、 Mo: 1.00~3.00% Ti: more than 0 and less than 1.00%, and Fe: 2.00~6.00%.
5. The austenitic alloy material according to claim 1 or claim 2, wherein the chemical composition thereof contains, in mass %, C: greater than 0 and less than 0.050%, Si: more than 0 and less than 0.50%, Mn: more than 0 and less than 0.50%, P: greater than 0 and less than 0.030%, S: greater than 0 and less than 0.015%, Cu: more than 0 and less than 0.50%, Cr:27.00~31.00%、 Fe: 7.00~15.00%, and Ni: 58.00~80.00%.
Citation Information
Patent Citations
Austenitic heat resistant steel
JP2017088957A